Systematic review of reports describing potential impact of the Sunshine Act on peer-reviewed medical publications. (3rd March 2016) - Toroser, Dikran; Robinson, Micah; Gegner, Julie; Smith, Geoff; Nilsen, Jon; Hyatt, Lucy; Johnson, Tracy; Hassan, Ali; Gatchalian, Christine
Abstract: Objective: The Physician Payments Sunshine Act, enacted in 2010, is intended to increase the transparency of relationships between US physicians and teaching hospitals and manufacturers of drugs, biologics, and medical devices. We examined current opinion regarding the impact of the Sunshine Act on peer-reviewed medical publications. Research design and methods: We searched indexed databases (NLM/PubMed, EMBASE, and Scopus) and nonindexed sources (lay and medical press, medical websites, congress abstracts) for articles published between January 2010 and June 2015 that contained terms indicative of content related to the Sunshine Act (e.g., 'Sunshine Act', 'open payment program'). Nine publication professionals then systematically reviewed identified articles for publications-related content. Main outcome measures: Quantification and characterization of publications that focused on the Sunshine Act and its implications for medical publishing. Results: Among 1200 indexed publications, 113 had content on the Sunshine Act. Thirty-one discussed its implications for publications; nine distinguished between financial and nonfinancial transfers of value. Of the 117 nonindexed publications with content on the Sunshine Act, 16 discussed implications for publications, and seven distinguished between financial and nonfinancial transfers of value. Reporting of such transfers of value was viewed as a potential barrier to participation in publications with industry support. Conclusions: There is limited literature on the impact of the Sunshine Act on peer-reviewed publications and limited physician awareness that publication support may be reported as a transfer of value.